2008
DOI: 10.1007/s00431-008-0882-z
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus (HPV) infection in children and adolescents

Abstract: Human papilloma viruses (HPV) are common pathogens associated with a wide range of cutaneous and mucosal infections in childhood. Different HPV types can cause common warts, genital warts, low-grade as well as high-grade squamous intraepithelial lesions. Anogenital warts represent an issue with legal and clinical implications and evaluation of children for the possibility of sexual abuse should be considered in all cases. Recurrent respiratory papillomatosis has also been associated with HPV infection in a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 71 publications
(120 reference statements)
1
52
0
5
Order By: Relevance
“…Papillomatosis in other sites of the body show a female predominance for genital (33% vs 67%) and cutaneous (49% vs 51%) papillomas and a male predominance for upper respiratory involvement (77% vs 23%). 24,[26][27][28] Multicentric conjunctival papillomas were more common in children and adolescents than in adults, and the numerous lesions coalesced to form massive papillomatosis in 1 patient ( Figure 1B). Ash 17 studied 245 conjunctival papillomas in patients of all ages (range, 1-97 years) and found that the most common location of conjunctival papilloma was the bulbar conjunctiva (42%).…”
Section: Commentmentioning
confidence: 99%
“…Papillomatosis in other sites of the body show a female predominance for genital (33% vs 67%) and cutaneous (49% vs 51%) papillomas and a male predominance for upper respiratory involvement (77% vs 23%). 24,[26][27][28] Multicentric conjunctival papillomas were more common in children and adolescents than in adults, and the numerous lesions coalesced to form massive papillomatosis in 1 patient ( Figure 1B). Ash 17 studied 245 conjunctival papillomas in patients of all ages (range, 1-97 years) and found that the most common location of conjunctival papilloma was the bulbar conjunctiva (42%).…”
Section: Commentmentioning
confidence: 99%
“…The possibility of hand transmission is suggested by the reports of children with anogenital warts who were considered to have acquired their infection from close family members or by their own hand warts. But this study applies to the cases with warts caused by low-risk HPV infection [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly thirty years ago, Gissmann and colleagues were the first team to detect DNA sequences from HPV types 6 and 11 in laryngeal papillomas (Gissmann et al, 1983). Laryngeal papillomatosis, also known as recurrent respiratory papillomatosis (RRP), is characterized by the recurrent growth of exophytic, wart-like lesions called papillomas, along the epithelium of the upper respiratory tract, such as the vocal cords, the arytenoids, the subglottis, the trachea and most commonly, the larynx (Lacey et al, 2006;Mammas et al, 2009). Although the RRPs are benign, their recurrent nature and location in the airways require frequent surgical removal and can cause significant morbidity and occasional mortality secondary to airway obstruction.…”
Section: The Recurrent Respiratory Papillomatosis (Rrp)mentioning
confidence: 99%